FORMULASI STRATEGI PENGEMBANGAN DIGITAL BANKING (STUDI KASUS BANK ABC): STRATEGIC FORMULATION OF THE DIGITAL BANKING DEVELOPMENT (CASE STUDY OF BANK ABC) - Haris Budiman; Kudang Boro Seminar; Imam Teguh Saptono (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2020)
Threat to banking industries, other than Fintech in sector of payment such as the GoPay, threat is also come out of Fintech and Startup in sector of loan such as the UangTeman. Revolution in digital technology produced by the Fintech and the Startup changes people’s behavior to access financial services, from coming to bank office to be an access in using smart phone. Objectives and research methods use qualitative and quantitative approaches as follows: to identify existing core competencies of the Bank ABC using the VRIO (Valuable, Rare, Inimitable, Organized to Capture Value) and recommendation of future competencies using the industry foresight; to formulate and to look into strategic alternative using the Porter's Five Force, the Internal-External matrix, the SWOT matrix, and the QSPM; to recommend road maps to strategic implementation of the digital banking using the AHP. Research results recommend 3 future competencies that the Bank ABC needs to have in the digital banking development from development of 13 existing core competencies by implication in competitive advantage. The main strategic alternative for calculation result of the AHP is reengineering bank products that are able to be marketed by the Bank ABC or the Fintech and the Startup. Based on calculation of the AHP, the main future competency is the Two-Way Digitalization. Keywords: core competency, digital banking, digital technology, fintech, industry foresight